CYTOGENETIC AND DNA CONTENT STUDIES OF ARMORED CATFISHES OF THE GENUS CORYDORAS (PISCES, SILURIFORMES, CALLICHTHYIDAE) FROM THE SOUTHEAST COAST OF BRAZIL - Oliveira, C.; Almeidatoledo, L. F.; Mori, L.; Toledofilho, S. A. (Soc Brasil Genetica, 1993)
Cytogenetic and DNA content studies were done on six nominal species of Corydoras from the southeast coast of Brazil. The data show that several nominal species present local populations with differences in karyotype or DNA content. There are at least two groups of Corydoras species with similar karyotypic structure in this region: the first composed by C. ehrhardti, C. nattereri and C. paleatus and the second composed of C. barbatus, C. macropterus and C. prionotos. These two groups of species are probably not derived directly from the same ancestral line. The speciation process of Corydoras species from the southeastern coast of Brazil is discussed.